Lymphoepithelioma‐like carcinoma of uterine cervix: Preoperative diagnosis and course in three cases. Issue 11 (10th August 2021) - Ikeda, Asami; Abiko, Kaoru; Emoto, Ikuko; Ujita, Mari; Takao, Yumi; Konishi, Ikuo
Abstract: Lymphoepithelioma‐like carcinoma of the uterine cervix is a rare variant of squamous cell carcinoma. Herein, we describe three cases of lymphoepithelioma‐like carcinoma of the uterine cervix and review relevant literature. All three patients initially presented with postmenopausal bleeding. Gross appearances were endophytic with ulcerated mucosa in case 1, exophytic with polypoid morphology in case 2, and unremarkable even using colposcopy and hysteroscopy in case 3. Magnetic resonance imaging demonstrated well‐demarcated cervical masses with high‐intermediate intensity on T2‐weighted images and high intensity on diffusion‐weighted images in all three cases. In case 3, biopsy referring to local information from magnetic resonance images was required for preoperative diagnosis. We reviewed the literature of 59 lymphoepithelioma‐like carcinoma cases in 19 papers published between 2001 and 2020. Preoperative diagnosis of lymphoepithelioma‐like carcinoma is sometimes challenging, although magnetic resonance imaging findings may help determine the location of the tumor and obtain a successful biopsy.